The Effect of Drilling Intervention on Increasing Shuttlecock Hit Accuracy in Adolescent Badminton Athletes (Aged 15-20 Years) - Ashari, Sani Bayu; Hazar, Fatih; Damayanti, Enarnimas; Khanina, Naila (Journal of Racket Sports Performance & Science (JRSPS), 2025)
Background: The accuracy of dropshot and smash shots is a crucial factor in the performance of young badminton athletes, but often shows inconsistency, requiring effective training methods. Research Objective: This study aims to analyze the effect of a drilling training program intervention on improving the accuracy of dropshot and smash shots in young badminton athletes. Methods: This study used a quasi-experimental design with a one-group pretest-posttest design. The study sample consisted of 30 youth athletes (aged 15-20 years) selected through purposive sampling. The intervention consisted of a structured drilling program (focusing on dropshot and smash) administered for 6 weeks at a frequency of 3 times per week. The test instrument used to measure accuracy before (pre-test) and after (post-test) the intervention was an adaptation of the Poole Overhead Stroke Accuracy Test, which assessed the accuracy of the shuttlecock landing in the target area (maximum score of 40 points). Results: Data were analyzed using a paired t-test with a significance level of α = 0.05. The results showed a significant increase in the average dropshot accuracy score from 24.80 ± 4.15 (pre-test) to 36.50 ± 3.90 (post-test). A significant increase also occurred in the accuracy of the smash from 26.10 ± 4.88 (pre-test) to 39.20 ± 4.02 (post-test). The significance value (p-value) for both variables was < 0.001, which is less than 0.05. Conclusion: It was concluded that drilling interventions had a significant effect on improving the accuracy of dropshot and smash shots in junior badminton athletes.